Isolation Enhancement of Four-Element Quad-Band MIMO Meander-Line Loaded Inverted-F Antennas for Sub-6 GHz Wireless Applications - Anupa Chatterjee; Manas Midya; Panuwat Janpugdee; Hsi-Tseng Chou (IEEE Access)
A set of compact sub-6 GHz four-element quad-band MIMO antennas with high inter-element isolations is presented. It is formed by four meander-line loaded inverted-F antenna (IFA) structures located in the four quarters and oriented perpendicularly to each other to exhibit both polarization and spatial diversities in MIMO applications. The orthogonality of polarization reduces the inter-element mutual coupling for basic good isolation which is further enhanced by introducing a modified swastika-shaped decoupling element in the middle of the four antennas and cutting slits loaded on the dielectric substrate’s four edges. The inter-element isolations are observed better than 20 dB at low frequencies and between (40-50) dB at higher frequencies. The measured radiation characteristics of the fabricated antenna prototype agree very well with the simulated results. The antenna set has an overall size of $24× 24× 0.8$ mm3 with an inter-element spacing of 2 mm, corresponding to less than a quarter wavelength at the lowest frequency band and still less than a half wavelength at the highest frequency band of operation. The antenna resonates in the following four bands: 2.85 GHz (S-band), 4.33 GHz (Radar altimeter), 5.5 GHz (WLAN), and 5.9 GHz (Wi-MAX, WLAN). The antenna gains are better than 6 and 5 dBi in most bands from the simulations and measurements, respectively, with measured efficiencies of better than 80%.